Karamah Menurut Shaykh Dr. Hj. Jahid Hj. Sidek - Ahmad Najaa' Mokhtar; Muhammad Khairi Mahyuddin; Syed Hadzrullathfi Syed Omar; Ahmad Atoa' Mokhtar; Mohd Shaifulbahri Abdullah (IAI Al-Mawaddah Warrahmah Kolaka, 2024)
Volume :2 No:2